Sustainable retail refrigeration - Evans, Judith A. (Judith Anne), 1962-; Foster, Alan M. (Malden, MA : Wiley-Blackwell, 2015)
Carbon emissions from the retail segment of the food cold chain are relatively high compared to other parts of the food cold chain. Studies have also shown that food temperature is less well controlled at the retail and consumer end of the cold chain. There is therefore considerable potential to optimize performance of refrigerated display cabinets and the refrigeration systems that are used to operate them to reduce carbon emissions and to improve food temperature control. Sustainable Retail Refrigeration draws together world experts on retail refrigeration. In a single resource, the authors cover the latest technologies and best current knowledge in the field. With increasing concerns about energy use and global warming gasses, retailers are increasingly being called to account for their actions. Sustainable Retail Refrigeration is a valuable reference to manufacturers, managers and policy makers, incorporating both a design and an operational perspective.
Title from resource description page (Recorded Books, viewed November 30, 2015).
Keywords: Technology; TECHNOLOGY & ENGINEERING -- Food Science; Technology; Electronic books